Characterization data on crops, production systems, abiotic constraints, population and poverty for farming system regions of the world. - Barona, Elizabeth; Guevara, Edward D.; Hyman, Glenn G. (2016)
This data set builds on a previous project that examined geographic targeting of agricultural research and development based on the coincidence of biophysical and socioeconomic conditions of drought prone crop production (Hyman et al., 2008). The data characterizes the farming systems of John Dixon’s global farming systems framework and map (Dixon et al., 2001). The data set comprises the spatial distribution of 63 farming systems overlaid on a map of the countries of the world to produce information for 544 combinations of farming systems and countries. Data is organized by the 63 farming systems and the 544 combinations of farming systems and countries. For each of these units, data has been compiled on crop area, crop yield, crop production, population, poverty, drought, heat, soil conditions and other information. The data set contains updated information not available in the previous study. This new data set has 42 crops mapped globally instead of 20 crops in the previous study. The new data includes crop data for the year 2005, whereas the previous study had year 2000 data. Population data was also updated to the year 2010.